Pengaruh Kualitas Layanan, Fasilitas dan Penetapan Harga Terhadap Kepuasan Jamaah Umroh pada PT Impressa Media Wisata Purwokerto - Murniati, Suci; Setiawan, Mulyo Budi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to test and analyze the influence of service quality, facilities, and pricing on pilgrim satisfaction partially and simultaneously at PT Impressa Media Wisata Purwokerto. The research method used is a quantitative method. The population in this study was the umrah pilgrims of PT Impressa Media Wisata in the 2025 season, with a sampling technique that focused on the 2025 milad package pilgrims so that a sample of 95 respondents was obtained. Data were collected through questionnaires and analyzed using multiple linear regression analysis methods through validity tests, reliability tests, coefficient of determination tests, F tests, and t tests. The results of the instrument testing showed that all statement items in the questionnaire were declared valid and reliable. The results of the partial regression test (t test) proved that: (1) service quality had a positive and significant effect on pilgrim satisfaction; (2) facilities had a positive and significant effect on pilgrim satisfaction; and (3) pricing had a positive and significant effect on pilgrim satisfaction. Furthermore, the results of the F test showed that service quality, facilities, and pricing together (simultaneously) had a significant effect on pilgrim satisfaction. The practical implications of this research emphasize the importance of synergy between aspects of service reliability, fulfillment of physical/non-physical facility eligibility, and transparency of adaptive pricing in order to optimize pilgrim satisfaction.